PENERAPAN DAN PELATIHAN SISTEM DISPLAY JADWAL SALAT DIGITAL BERBASIS WEBSITE MENGGUNAKAN RASPBERRY PI DI MASJID BAITUL MAQDIS - Rika Perdana Sari; Elva Susianti; Kartina Diah Kesuma Wardani; Muhammad Adlu; Muhammad Raihan Alifiandra; M Syahrul Iqbal; Dani Raditya Maulana; Hadid Zarid Nawfal (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The modernisation of mosque services represents the application of appropriate technology to support religious activities within the community. Before this program, the management of Masjid Baitul Maqdis in Pekanbaru displayed the prayer schedule manually on an announcement board, which was often not updated promptly. This condition resulted in inaccuracies in providing prayer time information to congregants. Based on this issue, this community service activity aimed to implement and provide training on using a web-based digital prayer schedule display system utilizing Raspberry Pi as the primary control device. The implementation process consisted of several stages, including the preparation stage, the system deployment stage, and the training stage for mosque administrators. Evaluation was conducted through direct observation and interviews with administrators to assess the system’s ease of use and effectiveness. The results showed that through automatic synchronization with a location-based prayer time API service, enabling real-time updates on the mosque display. This community service activity has contributed to enhancing the digital literacy and independence of mosque administrators in managing the system, thereby reducing their reliance on external parties. Furthermore, the activity has positively impacted the mosque’s operational efficiency and the satisfaction of its congregants with digital information services.